Fitness for Service (FFS) and Fatigue Assessment for Shell Distorted Steel Storage Tank Based on API 579-1/ASME FFS-1 - Herucakra, Wira, Sr. Structure Engineer; Prasetyo, IC Farid Hadi; Rizkhita, Alviani Rahma; Adnyani, Luh Putri (UI Scholars Hub, 2024)
A shell distortion was occurred due to incorrect in the welding procedure during construction of a new built above ground steel storage tank. The assessment level 1 then performed referred to original construction code of API Standard 650 was performed, the roundness data of tank plate was obtained through to laser scanning survey, and the result on assessment level 1 known that the minimum radius of measured point is exceeding the radius tolerance. This unacceptable condition of assessment level 1 requires to be performed the higher level of assessment. A fitness for service assessment level 3 for tank 1000 KL was performed based on API 579-1/ASME FFS-1 Fitness For service Part 8 Assessment of Weld Misalignment and Shell Distortions, The stress analysis procedure is in accordance to on API 579-1/ASME FFS-1 Fitness For service Annex 2D Stress Analysis Overview for FFS Assessment, the load case condition considered under combined static, environmental and seismic loading condition and the acceptance criteria is in accordance with ASME B&PV Code - Section VIII - Division 2, API Standard 650 and ASCE 7.